Building effective learning environments : a framework for merging the best of old and new practices - Krahenbuhl, Kevin S. (New York : Routledge, 2021)
'Teachers are bombarded with trends and competing ideas. This book provides a framework to help you find the right balance between new and old instructional practices, so you can design learning environments that truly enhance learning. The author shares key research-based principles to engage and extend learning, and he debunks common myths. He then shows how to use a classical method and how to engage with new ideas and evidence to create the most effective learning environment. Each chapter offers reflection and application questions you can use independently or in book studies to get the most out of your reading. Written for teachers of any grade level, the book contains applications and examples across content areas so you can see how to implement the ideas in your own classroom or school'--
Includes bibliographical references.
Keywords: Instructional systems -- Design; Effective teaching; Classroom environment